TWO LEVELS OF STUDENTS 'INTELLECTUAL AND EMOTIONAL DEVELOPMENT IN THE PROCESS OF MASTERING THEORETICAL FUNDAMENTALS METHODS OF TEACHING PHYSICS (Pedagogy of Higher and Secondary Education, 2011)
Two levels of intellectual and emotional development of students in learning of the theoretical foundational Physics learning were revelated. Trends of efficiency of intellectual and emotional development of pupilsin learning of Rhysics were analyzed.
Keywords: physics learning; intellectual development; emotional motivated development